A Companion of Feminisms for Digital Design and Spherology - Windle, Amanda (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book questions if spherology is a philosophy for designers, giving guidance on ways to read Spheres, how to approach the trilogy's indexicality, and apply the key tropes and ethics of atmospheres to digital design. Each chapter includes a design-in, that is a practical entry point into the many tropes of Spheres including- bubbles, globes and foam. The book also applies spherology to an atmosphere design issue involving endangered species and geospatial threats to the environment. Spherology refers to the Spheres trilogy by the philosopher Peter Sloterdijk, which traces spherical ideas, theories, sensations and feelings related to the philosophical concept of 'being' and the human-centered position of 'being-in'. It is the first cynical, feminist companion of spherology to take a practice-led approach and to cover all three controversial volumes to with and against Spheres. Windle draws on feminist science and technology studies (STS) through parody within reading, writing and design practices. Design provides navigation so that academics and students can engage with spherology through an embodied concern with digital materiality. As a feminist companion for today's design issues, the book is an essential read for feminist STS scholars, design practitioners and digital R&D specialists working both in industry and academia, including more specifically data visualisers, interface and interaction designers.